2019
DOI: 10.1038/s41598-019-44993-8
|View full text |Cite
|
Sign up to set email alerts
|

Nematode-free agricultural system of a fungus-growing termite

Abstract: Fungus-growing termites forage dead plant materials from the field to cultivate symbiotic Termitomyces fungi in the nest. Termite foraging behavior and the entry of symbiotic arthropod inquilines may transfer nematodes into a nest and adversely affect fungus production. To test whether nematodes were transferred to fungus gardens by termites and inquilines, we examined the occurrence of nematodes in fungus gardens, five termite castes, and nine species of inquilines of a fungus-growing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…66 In addition, more than 12 species of invertebrates, including minute bark beetles, rove beetles (Order: Coleoptera), fungus gnats, phorid flies (Order: Diptera), and silverfishes (Order: Thysanura), were reported to rely on the nutrition from O. formosanus or their fungus gardens. 67,68 Predictably, population suppression of fungus-growing termites would lead to the following consequences: (i) reduction of the decomposition rates of litters, and (ii) reduction of diversity of vertebrates and invertebrates in the forest ecosystem. We suggest avoiding applying termite control practices in natural forests.…”
Section: Effects Of Baiting On Sympatric Termite and Fungimentioning
confidence: 99%
“…66 In addition, more than 12 species of invertebrates, including minute bark beetles, rove beetles (Order: Coleoptera), fungus gnats, phorid flies (Order: Diptera), and silverfishes (Order: Thysanura), were reported to rely on the nutrition from O. formosanus or their fungus gardens. 67,68 Predictably, population suppression of fungus-growing termites would lead to the following consequences: (i) reduction of the decomposition rates of litters, and (ii) reduction of diversity of vertebrates and invertebrates in the forest ecosystem. We suggest avoiding applying termite control practices in natural forests.…”
Section: Effects Of Baiting On Sympatric Termite and Fungimentioning
confidence: 99%
“…Many symbiotic termitophiles and inquilines are also found inside termite nests (Carrijo et al ., 2012; Kanzaki et al ., 2019), especially beetles (Costa & Vanin, 2010), ants (Diehl et al ., 2005), spiders (DeVisser et al ., 2008), other termite species (da Cunha & Morais, 2010; Darlington, 2012), caterpillars, flies, mites, bugs, and millipedes (Cai et al ., 2017; Kanzaki et al ., 2019). However, the dependence of these associations may range from facultative to obligatory (Cristaldo et al ., 2012).…”
Section: Termitophiles Associated With Termitesmentioning
confidence: 99%
“…Recently, Kanzaki et al . (2019) assumed that the entry of symbiotic arthropods may transfer nematodes into the termite colony and affect the production of the fungus garden. Specifically, they tested the nine species of termitophiles of the fungus‐growing termite Odontotermes formosanus and found that numerous nematodes were present under the beetle elytra.…”
Section: The Role Of Termite‒termitophile Interactions In the Symbiotic Systemmentioning
confidence: 99%
See 2 more Smart Citations